Managing Organizational Conflict for Institutional Effectiveness: Evidence from Public Secondary Schools - Oksok, Nolito (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined conflict management and its relationship with organizational effectiveness in public secondary schools in the First Congressional District of Zamboanga del Norte during School Year 2024–2025. Anchored in Robbins’ Conflict Theory, particularly the interactionist perspective, it assessed conflict occurrence, prevention, resolution, and stimulation, as well as administrators’ competence in conflict management and organizational effectiveness in terms of awareness, flexibility, and productivity. A descriptive-correlational quantitative design was employed involving public secondary school administrators and teachers selected through purposive and proportionate random sampling. Data were gathered using a structured, expert-validated, and reliability-tested survey questionnaire and analyzed through frequency counts, percentages, means, standard deviations, and Pearson product-moment correlation at the 0.05 level of significance. Findings showed a generally high level of conflict management, with prevention and resolution as the strongest dimensions, while conflict stimulation remained moderately developed. Administrators demonstrated high competence in conflict prevention and resolution but moderate competence in conflict stimulation. Organizational effectiveness was high across awareness, flexibility, and productivity. Significant relationships were found between conflict management and organizational effectiveness and between administrators’ conflict-management competence and organizational effectiveness. The study concludes that effective conflict management strengthens communication, collaboration, adaptability, productivity, and institutional performance. It recommends sustained administrator-development programs, transparent communication, collaborative decision-making, and greater attention to constructive conflict engagement. The study supports SDG 4 on Quality Education and SDG 16 on Peace, Justice, and Strong Institutions by promoting effective educational leadership and responsive institutional governance. It contributes to educational, institutional, governance, and socio-organizational sustainability by supporting resilient, collaborative, and productive school environments.